Keynesian monetary theory and the Cambridge school - PATINKIN, D. (PSL Quarterly Review, 2013)
The monetarist revival of the last decade and more has been accompanied by a renewed interest in the nature of the quantity theory before Keynes. In this connection modern-day adherents of this theory seem to have claimed too much for it, and correspondingly too little for the Keynesian theory. The exaggerated claims for the quantity theory have expressed themselves in the attempt to present Keynes’ monetary theory not as a new theory, but as a variation on the Cambridge cash-balance theory. In the present article, the author examines this contention, and on the basis of this examination comes to reject it. JEL: B31, B22